Hypoxia and the hypoxia-regulated transcription factor HIF-1α suppress the host defence of airway epithelial cells. Issue 4 (May 2017) - Polke, Markus; Seiler, Frederik; Lepper, Philipp M; Kamyschnikow, Andreas; Langer, Frank; Monz, Dominik; Herr, Christian; Bals, Robert; Beisswenger, Christoph
Chronic diseases of the respiratory tract, such as cystic fibrosis, are associated with mucosal and systemic hypoxia. Innate immune functions of airway epithelial cells are required to prevent and control infections of the lung parenchyma. The transcription factor hypoxia-inducible factor 1α (HIF-1α) regulates cellular adaptation to low oxygen conditions. Here, we show that hypoxia and HIF-1α regulate innate immune mechanisms of cultured human bronchial epithelial cells (HBECs). Exposure of primary HBECs to hypoxia or the prolyl hydroxylase inhibitor dimethyloxaloylglycine (DMOG) resulted in a significantly decreased expression of inflammatory mediators (IL-6, IFN-γ-induced protein 10) in response to ligands for TLRs (flagellin, polyI:C) and Pseudomonas aeruginosa, whereas the expression of inflammatory mediators was not affected by hypoxia or DMOG in the absence of microbial factors. Small interfering RNA-mediated knockdown of HIF-1α in HBECs and in the bronchial epithelial cell line Calu-3 resulted in increased expression of inflammatory mediators. The inflammatory response was decreased in lungs of mice stimulated with inactivated P. aeruginosa under hypoxia. These data suggest that hypoxia suppresses the innate immune response of airway epithelial cells via HIF-1α.